PENGARUH PROFITABILITAS, INTEREST COVERAGE RATIO, RETAINED EARNING, DAN PERTUMBUHAN PERUSAHAAN TERHADAP PERINGKAT OBLIGASI PADA PERUSAHAAN NON KEUANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2012-2014 - Teuku Muhammad Syawal; Fachrizal Fachrizal (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2016)
The aim of this study is to examine the influence of profitability, interest coverage ratio, retained earning, and growth to bond ratings on non-financial companies listed in Indonesia stock exchange based on the information from the annual financial statement, Indonesia capital market directory, and Indonesia bond market directory with observation ranging from 2012 until 2014. The study type used in this study is hypothesis testing. The type of data used is secondary data. The study employed logistic regression analysis on a targeted population of 25 non-financial companies listed on the Indonesia Stock Exchange. The statistical tools used were SPSS (PASW Statistics) 18.0 version. The results shows that financial information regarding to the companies’ profitability (ROA and ROE) has positive influence to bond ratings, interest coverage ratio has positive influence to bond ratings. Then, retained earning has positive influence to bond ratings, while growth has negative influence to bond ratings. Simultaneously, all of the independent variables has influence the bond ratings. Keywords: Profitability, Interest Coverage Ratio, Retained Earning, Growth, Bond Ratings